Step
*
of Lemma
sv-bag-equals-list
∀[A:Type]. ∀[L:A List]. ∀[bs:bag(A)].  (L = bs ∈ (A List)) supposing ((L = bs ∈ bag(A)) and single-valued-list(L;A))
BY
{ (Auto THEN newQuotD 3 THEN (EqTypeHD (-1) THENA Auto) THEN (BLemma `permutation-sv-list` THEN Auto)⋅) }
1
1. A : Type
2. L : A List
3. A List ∈ Type
4. ∀as,b1:A List.  (permutation(A;as;b1) ∈ Type)
5. ∀as:A List. permutation(A;as;as)
6. a : Base
7. b : Base
8. c : a = b ∈ pertype(λas,bs. ((as ∈ A List) ∧ (bs ∈ A List) ∧ permutation(A;as;bs)))
9. a ∈ A List
10. b ∈ A List
11. permutation(A;a;b)
12. single-valued-list(L;A)
13. L = a ∈ pertype(λas,bs. ((as ∈ A List) ∧ (bs ∈ A List) ∧ permutation(A;as;bs)))
14. L ∈ A List
15. a ∈ A List
16. permutation(A;L;a)
⊢ single-valued-list(a;A)
Latex:
Latex:
\mforall{}[A:Type].  \mforall{}[L:A  List].  \mforall{}[bs:bag(A)].    (L  =  bs)  supposing  ((L  =  bs)  and  single-valued-list(L;A))
By
Latex:
(Auto
  THEN  newQuotD  3
  THEN  (EqTypeHD  (-1)  THENA  Auto)
  THEN  (BLemma  `permutation-sv-list`  THEN  Auto)\mcdot{})
Home
Index